Perusing the Contemporary Tendencies in Employees’ Job Performance Studies: A Bibliometric Analysis of Research Trends, 2013–2023 - Abriham Ebabu Engidaw; Weikang Zou; Jing Ning; Grillo Francesco; Jiang Hanchen (SAGE Open)
This study examined the bibliometric indicators of employee job performance articles published between 2013 and 2023, which were taken from the Web of Science database, and specifically aimed to explore the trends and themes of job performance research, the characteristics of authors, publications, nations and institutions, and the particular authorship partnerships and references that are frequently cited in the field of employee performance. The research performed descriptive and bibliometric analyses using the R-Studio data analysis tool, with 983 full-text articles selected based on their relevance to the study subject. The study finds that there has been a dramatic increase in interest in employees’ job performance studies, growing authorial collaborations, country collaborations, citations, and co-citations, though most of these research activities are dominated by researchers from fewer countries, such as China, the USA, and Korea. And, according to the result, it is evident that the majority of highly cited papers in the field originate from the United States and China; in contrast, the citation rates of publications from other countries are notably lower. This present research is expected to contribute to the expanding body of knowledge and practice on employees’ job performance, enable the discovery of new trends in this area, and identify for the scientific community the main research directions that have been explored.